2015
DOI: 10.1016/j.bioelechem.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Thromboresistant/anti-biofilm catheters via electrochemically modulated nitric oxide release

Abstract: Inexpensive nitric oxide (NO) release strategies to prevent thrombosis and bacterial infections are desirable for implantable medical devices. Herein, we demonstrate the utility of electrochemically modulated NO release from a catheter model using an inner copper wire working electrode and an inorganic nitrite salt solution reservoir. These catheters generate NO surface fluxes of >1.0×10−10 mol min−1 cm−2 for more than 60 h. Catheters with an NO flux of 1.1×10−10 mol min−1 cm−2 are shown to significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 47 publications
2
56
0
Order By: Relevance
“…pathways. 132 Recently, it was demonstrated that nitrite can also be used to generate NO via electrochemical reduction at an electrode surface with either Cu(I) ion generated from oxidation of Cu 0 145,146 or via the use of Cu(II)-ligand complexes that mimic the active site of nitrite reductase (e.g., Cu(II)-tri(2-pyridylmethyl)amine, Cu(II)TPMA). 147 …”
Section: Nitric Oxide (No) To the Rescuementioning
confidence: 99%
See 2 more Smart Citations
“…pathways. 132 Recently, it was demonstrated that nitrite can also be used to generate NO via electrochemical reduction at an electrode surface with either Cu(I) ion generated from oxidation of Cu 0 145,146 or via the use of Cu(II)-ligand complexes that mimic the active site of nitrite reductase (e.g., Cu(II)-tri(2-pyridylmethyl)amine, Cu(II)TPMA). 147 …”
Section: Nitric Oxide (No) To the Rescuementioning
confidence: 99%
“…The Cu + ion is generated from oxidation of a copper wire 145,146 or the reduction of copper(II)-tri(2-pyridylmethyl)amine (Cu(II)TPMA) complex. 147 The electrochemically generated NO can be modulated by changing the potentials applied to the electrodes and can achieve between 0.5 and 3.5 × 10 −10 mol cm −2 min −1 , which is in the range of physiological relevant levels of NO released by the endothelial cells.…”
Section: Polymer-based Strategies For No Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Some more notable accomplishments utilizing NO include a reversal of hypoxic pulmonary vasoconstriction using inhaled NO, the development of an antimicrobial sol-gel for coating biomaterials used in implants, and an electrochemical oxygen probe which uses NO as an anticlotting agent [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the leaching of NO donors and/or byproducts into the bloodstream, and to produce very controllable NO generation over prolonged time, Ren et al [67] reported improvement in in vivo analytical performance of intravascular analytical sensors by coupling them with a new electrochemical method of NO generation. This method involves electrochemical reduction of inorganic nitrite ions catalyzed by a copper(II)-ligand complex, copper(II)-tri(2-pyridylmethyl)amine (Cu(II)TPMA; see structure in Figure 2).…”
Section: Nitrite For No Generationmentioning
confidence: 99%